Bioaccumulation of Iron in Plants and Their Possibilities as a Tool for Exploration of Hematite Ores - Parajuli, Ishor; Chettri, Mukesh Kumar (Amrit Research Journal, 2020)
Relation of plant diversity with iron ore deposit area in Dhaubadi, Hupsekot rural municipality-5, Nawalparasi district, has been investigated in this study to explore good indicator and accumulator among plants. To identify this, plant diversity, iron accumulation in soil and plants growing on them at different plots were measured. Spermacoceae alata, Anaphalis busua, Isodon coesta and Salvia sclarea were common herbs in all plots and out of them Spermacoceae alata had the highest importance value index (IVI) value among herbs. Among the shrubs Ageratina adenophora, Maesa chisia, Osbekia stellate and Elsholtzia blanda were common in all the plots and of them Ageratina adenophora showed the highest IVI. Plant like Elsholtzia blanda and Anaphilis busua were identified as good indicator of iron deposits because of high amount of iron in their body, especially roots. Among all the sites, Begonia picta at the core area (Site A) had the highest iron accumulation, and most plants found there like Cyanotis vaga, Hypericum japonicum, Begonia picta, Gonostegia hirta, Trumphetta rhomboidea, Osbekia stellata and Isodon coesta had bronze coloration in leaves. The bronze coloration in leaves among plants has been identified as a good indicator to ascertain iron ore deposits.